Ethyl N-(2-benzoyl-3-oxo-3-phenylpropanoyl)carbamate - Akkurt, Mehmet (International Union of Crystallography, 2013)
In the title compound, C(19)H(17)NO(5), the dihedral angle between the phenyl groups is 79.55 (15)°. The terminal ethoxy group is disordered over two orientations in a 0.873 (6):0.127 (6) ratio. In the crystal, molecules are linked by N—H⋯O and C—H⋯O hydrogen bonds into [001] chains which incorporate R (1) (2)(6) loops. A very weak C—H⋯π contact also occurs.